2010
DOI: 10.1589/jpts.22.23
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Physical Function in Community-Dwelling People Aged 50-79 Years

Abstract: Abstract.[Purpose] We aimed to obtain the mean values for physical function tests in healthy communitydwelling people aged 50-79 years and to compare these values between age decades. [Subjects and Methods] We recruited 172 healthy community-dwelling people, who provided their written consent. Grip strength (GS), isometric knee extension torque (IKET), and the times for performing the sit-to-stand test (STS) and timed up-and-go test (TUG) were used as indicators of physical function. Maximum force (Fmax) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…A total of 12 studies fulfilled the inclusion criteria: eight studies 13,[19][20][21][22][23][24][25] provided data on maximum effort (Table 1), and five studies 14,22,[27][28][29] provided data on the usual pace (Table 2). Studies with maximum effort data involved 2903 subjects (men 1083, women 1820), and studies with usual pace data involved 2396 subjects (men 815, women 1343, unknown 238).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies fulfilled the inclusion criteria: eight studies 13,[19][20][21][22][23][24][25] provided data on maximum effort (Table 1), and five studies 14,22,[27][28][29] provided data on the usual pace (Table 2). Studies with maximum effort data involved 2903 subjects (men 1083, women 1820), and studies with usual pace data involved 2396 subjects (men 815, women 1343, unknown 238).…”
Section: Resultsmentioning
confidence: 99%
“…This marked increase in life expectancy increases the morbidity from chronic diseases 2 ) , depression 3 ) , and worsens physical performance and quality of life 4 ) . Besides, ageing may affect physical performance of older adults, evoking negative impacts on their behavior and consequent changes in lifestyle, causing them to become dependent 5 ) . Several studies have reported that the loss of functional capacity in elderly people is usually related to the presence and complexity of comorbidities 6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It is common knowledge that an individual's height (Kenny et al, 2008), weight (Kenny et al, 2008), body mass index (Corish and Kennedy, 2003) and muscle strength (Tsubaki et al, 2010) will decrease with ageing. They have shown that the decrease in muscle size is positively correlated with a decrease in hand grip strength.…”
Section: Introductionmentioning
confidence: 99%